1997
DOI: 10.1104/pp.113.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Dormancy in Developing Sorghum Seeds

Abstract: YPreharvest sprouting is one of the main problems encountered in sorghum (Sorghum bicolor [L.] Moench.) production, particularly when seed maturation takes place under damp conditions. Although it is known that genetic variability for sprouting resistance exists, the underlying physiological mechanisms are poorly understood. Sprouting resistance in sorghum is related to the maintenance of a sufficient dormancy level during development (Steinbach et al., 1995). Indeed, although isolated embryos from both suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 14 publications
3
56
0
1
Order By: Relevance
“…Although it became clear from these and many other experiments that manipulating ABA has an impact on dormancy, differences in endogenous ABA content in cereal varieties do not usually appear to be linked to the observed differences in dormancy (Walker-Simmons, 1987;Steinbach et al, 1997). Instead, responsiveness of isolated embryos to exogenous ABA is highly correlated with dormancy expressed in the intact grains from several species, such as wheat (Walker-Simmons, 1987;Morris et al, 1989;Gerjets et al, 2010), barley (Wang et al, 1995;Benech-Arnold et al, 1999Leymarie et al, 2008;Barrero et al, 2009), oat (Corbineau et al, 1991, sorghum (Steinbach et al, 1995) and rice (Gianinetti and Vernieri, 2007).…”
Section: Hormonal Regulation Of Dormancymentioning
confidence: 99%
See 2 more Smart Citations
“…Although it became clear from these and many other experiments that manipulating ABA has an impact on dormancy, differences in endogenous ABA content in cereal varieties do not usually appear to be linked to the observed differences in dormancy (Walker-Simmons, 1987;Steinbach et al, 1997). Instead, responsiveness of isolated embryos to exogenous ABA is highly correlated with dormancy expressed in the intact grains from several species, such as wheat (Walker-Simmons, 1987;Morris et al, 1989;Gerjets et al, 2010), barley (Wang et al, 1995;Benech-Arnold et al, 1999Leymarie et al, 2008;Barrero et al, 2009), oat (Corbineau et al, 1991, sorghum (Steinbach et al, 1995) and rice (Gianinetti and Vernieri, 2007).…”
Section: Hormonal Regulation Of Dormancymentioning
confidence: 99%
“…For example, maize kernels are viviparous if the ABA signal is reduced or abolished (as in vp5 and vp1 mutants, which are ABA deficient and ABA insensitive, respectively, or with the application of fluridone, an ABA biosynthesis inhibitor) . Spraying young sorghum panicles with fluridone reduced ABA content in the grains and anticipated dormancy release, making a sprouting-resistant line behave as a sprouting-susceptible one (Steinbach et al, 1997). Several rice mutants exhibit vivipary and photooxidation in the light.…”
Section: Hormonal Regulation Of Dormancymentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat, barley, and sorghum cultivars that are susceptible to pre-harvest sprouting, there is a relative sensitivity of the embryo to ABA as compared to resistant cultivars, generally in the absence of any substantial differences in ABA content, or a higher ABA content in the susceptible cultivars [5,6]. Interestingly, the expression pattern of the sorghum VP1 gene is different in two cultivars genotypes exhibiting differential resistance to preharvest sprouting at physiological maturity.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, in the embryos of the susceptible cultivar, transcripts encoding VP1 peak at a relatively early stage of grain development (20 days after pollination), whereas the peak in the resistant cultivar occurs at much later developmental stages, when seed maturation is almost complete [5]. Tanner showed that PHS in corn was linked with deficiency of molybdenum [6]. Premature germination in maize was eliminated by Mo applications to the soil or the leaves.…”
Section: Introductionmentioning
confidence: 99%